Effect of Seed Coating and Packaging Material on Viability and Vigor of Soybean Seed in Room Temperature Storage - Olaf Ingmar; Setiyono Setiyono; Dyah Ayu Savitri; Noer Novijanto (Journal of Applied Agricultural Science and Technology, 2023)
Soybean seed procurement was challenging due to the quality degradation during the seed storage period. Seed coating is necessary in order to overcome the leakage of seed metabolites. Seed coating has to be supported by a storage package that can protect the seed from temperature and humidity fluctuations in storage. This study aimed to determine the effect of seed coating using antioxidants and storage packaging to maintain the viability and vigor of soybean seeds. The experiment was carried out factorially with the basic pattern of Completely Randomized Design (CRD) and was repetitively replications by three times. The first factor was seed coating, which consisted of 4 levels such as M1=no coating, M2= 3% of Arabic gum + ascorbic acid, M3= 3% of Arabic gum + tocopherol, and M4= 3% of Arabic gum + mangosteen peel extract. The second factor was that the storage package consisted of 3 levels, which were N1= aluminum foil, N2= polyethylene plastic, and N3= plastic sack. The interaction between the seed coating material and storage package on seed moisture content with the best treatment was seed coating using ascorbic acid and aluminum foil package, seed coating treatment carried out the best effect without implementing the seed coating, and the storage package treatment that presented the best effect was aluminum foil package.